Back Cover: Total Synthesis of (−)‐Salinosporamide A via a Late Stage C−H Insertion (Angew. Chem. Int. Ed. 30/2019). Issue 30 (9th July 2019) - Gholami, Hadi; Kulshrestha, Aman; Favor, Olivia K.; Staples, Richard J.; Borhan, Babak
Abstract : A total synthesis of (−)‐Salinosporamide A is presented by B. Borhan and co‐workers in their Communication on page 10110 ff., with a tandem aza Payne/hydroamination reaction of a precursor alkynyl aziridinol being used to create a pyrrolidinone core with functionalities in place for further elaboration. A carbene generated from a vinyl bromide leads to intramolecular C−H insertion at a sterically demanding carbon center to forge the required C−C bond.